Manipulation And Persuasion Through Language Features In Fake News - Agus Ari Iswara; Kadek Agus Bisena (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
This study attempts to describe the use of language features in hoaxes to manipulate facts and describe their persuasive power in influencing readers. This research is a qualitative descriptive study. This research data is documented from turnbackhoax.id. This site was chosen because it is one of the most popular hoax repellent sites in Indonesia. Documentation was the method of data collection. Data were collected then classified, organized, and then analyzed using theoretical concepts. Theory used to analyze language manipulation in this research is Barton and Lee's theory of language features and Searle theory of speech acts. Data and analysis are presented in tables with brief descriptions. The results of this study indicates that hoax maker use language features in manipulating facts, those are (1) acronyms and initialisms, (2) word reduction, (3) letters or numbers, (4) stylized/unconventional spelling, (5) emoticons, (6) stylized/unconventional punctuation, and (7) images or photographs. Furthermore, it is found the use of assertive, expressive and directive speech acts to build persuasive power to influence the reader. The results of this study can be used as a reference in seeing the characteristics of language manipulation on hoaxes so that people can maximize the use of their logic and intellectual as a system of verifying information to determine the truth of information, knowing the information is fact or fake, distinguishing an information is a hoax or fact.